A high efficiency buck converter for IoT sensors - Mo, Mingwei (Nanyang Technological University, 2024)
With the surge in Internet of Things (IoT) applications, from smart homes to Industry 4.0 and healthcare, there's a critical need for power-efficient DC-DC converters to support the wide operational spectrum of IoT devices, especially those powered by Li-ion batteries. Powering a vast network of IoT devices presents challenges due to their limited battery capacity and the impracticality of frequent battery replacements. IoT sensors mostly operate in sleep mode, so the DC-DC converter's load current can drop to the microampere level. When the system is activated for data collection and processing, the load current may spike to tens of milliamperes. Thus, it's essential for the DC-DC converter to accommodate a broad spectrum of load currents, ensuring versatility and reliability in various operational states. This dissertation presents the design of a buck converter implemented in a Global Foundries (GF) 55nm CMOS process for IoT sensor applications. The converter accommodates the full 2.5V to 4.2V input voltage range of Li-ion batteries and generates a 1.2V output voltage with a load current in the range of 10 μA to 100 mA, which is optimized for light load conditions to prolong battery life. The proposed design integrates control blocks, including a dead time control circuit for non-overlapping signals, a capacitively coupled level shifter for high-voltage CMOS compatibility, and a zero current detector to minimize reverse conduction loss and enhance overall efficiency. Simulation results show that the proposed converter achieved efficiencies above 80% across a broad load current range from 12 μA to 100 mA with a peak efficiency of 92.7% at 10 mA, while the nominal quiescent current measured to be 450 nA.